Dedifferentiated carcinoma with clear cell carcinoma of the endometrium: A case report. Issue 9 (30th June 2017) - Lee, Seung Eun; Park, Ha young; Shim, Seung‐Hyuk; Kim, Wook Youn
Abstract : Endometrial dedifferentiated carcinoma consists of a combination of undifferentiated and differentiated carcinomas. To date, clear cell carcinoma components in endometrial dedifferentiated carcinoma have not been reported. We report the first case of endometrial dedifferentiated carcinoma with clear cell carcinoma in a 58‐year‐old woman. The uterine corpus was completely replaced and enlarged by a heterogeneous mass. The endometrial cut surface showed a yellowish papillary growing mass involving endometrium and deeper myometrium. Microscopically, the three components (endometrioid carcinoma, FIGO grade 1, clear cell carcinoma and undifferentiated carcinoma) were noted with differentiated carcinoma components lining the endometrial cavity, while undifferentiated carcinoma components were identified in deeper endometrium and myometrium. Our histologic diagnosis was supported by the pattern of immunoreactivity. Tumor cells showed loss of expression of MLH1/PMS2 protein and displayed high microsatellite‐instability in all three components. Furthermore, all three components including clear cell carcinoma had loss of PTEN and ARID1A expression. Our observations suggest that the three components derived from a monoclonal origin, as the three components had in common specific genetic alterations.